1991
DOI: 10.1002/jab.770020307
|View full text |Cite
|
Sign up to set email alerts
|

Bone graft and bone graft substitutes: A review of current technology and applications

Abstract: The morbidity associated with autogenous bone graft harvest and the recent concern regarding the transmission of live virus through use of allografts, have been the impetus for research into a variety of materials that could take the place of these standard materials for bone grafting. The positive results reported with various ceramics and/or bone derivatives suggest the possibility of a material with osteoconductive and/or osteoinductive properties for use with or in place of bone graft. This review discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
595
2
15

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 939 publications
(625 citation statements)
references
References 176 publications
13
595
2
15
Order By: Relevance
“…37 This biomaterial represents purified bovine extracellular calcified bone matrix and is regarded as having physicochemical properties similar to those of autologous bone grafts, which are considered to be the "gold standard" for bone regeneration. 1,2,42 As it has been shown that the resorbability of this xenogeneic material is delayed, the presented results raise the question of whether the low numbers of multinucleated giant cells in the case of the analyzed biphasic materials also lead to a low rate of degradation and therefore a prolonged material standing time. 37,43 However, the increase of the numbers of MNGCs and especially of their TRAP-positive subforms at the end of the study period in the case of the small-sized BC 400-700 are interesting.…”
Section: 41mentioning
confidence: 85%
See 1 more Smart Citation
“…37 This biomaterial represents purified bovine extracellular calcified bone matrix and is regarded as having physicochemical properties similar to those of autologous bone grafts, which are considered to be the "gold standard" for bone regeneration. 1,2,42 As it has been shown that the resorbability of this xenogeneic material is delayed, the presented results raise the question of whether the low numbers of multinucleated giant cells in the case of the analyzed biphasic materials also lead to a low rate of degradation and therefore a prolonged material standing time. 37,43 However, the increase of the numbers of MNGCs and especially of their TRAP-positive subforms at the end of the study period in the case of the small-sized BC 400-700 are interesting.…”
Section: 41mentioning
confidence: 85%
“…1,2 Calcium phosphates, specifically hydroxyapatite (HA) and b-tricalcium phosphate (b-TCP), are primarily used because of their chemical similarity to the calcified bone matrix and the related osteoconductive regeneration mechanisms. 3,4 However, it has been shown that these 2 ceramics exhibit different resorption patterns characterized by different dissolution properties and degrees of induction of phagocytosis based on mono-and multinucleated cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ripamonti et al (1989) reported bone induction in a composite allogeneic bone/alloplastic implant; Zhang et al (1991), Osborn (1991), and Ripamonti (1991a) discovered bone formation at ectopic sites after implantation of porous calcium phosphate ceramic materials in dogs and baboons. Later, osteoinductive bioceramics began to be reported by different labs in pigs, sheep, rabbits, and other large animal models all over the world (Damien and Parsons, 1991;Toth et al, 1993;Li et al, 1994;Yuan et al, 2000;2001a;Nihouannen et al, 2005;Ye et al, 2007;Fellah et al, 2008). Since then, generous attention was paid to these kinds of biomaterials, such as synthetic hydroxyapatite ceramics (HA), porous biphasic calcium phosphate ceramics (BCP), tricalcium phosphate ceramics (TCP), calcium pyrophosphate ceramics, and coralderived hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods have severe limitations and thus impose high cost on the health care system. The shortcomings associated with autograft include severe pain, morbidity of the harvested site, structural and anatomical problems, and high rate of resorption during healing [1,2]. Likewise, allograft may elicit disease transmission and rejection, further compounded by shortage of donors [3,4].…”
Section: Introductionmentioning
confidence: 99%